2015
DOI: 10.1128/jcm.01156-15
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Mycoplasma pneumoniae: Genotyping Using Single Nucleotide Polymorphisms and SNaPshot Technology

Abstract: i Molecular typing of Mycoplasma pneumoniae is an important tool for identifying grouped cases and investigating outbreaks. In the present study, we developed a new genotyping method based on single nucleotide polymorphisms (SNPs) selected from the whole-genome sequencing of eight M. pneumoniae strains, using the SNaPshot minisequencing assay. Eight SNPs, localized in housekeeping genes, predicted lipoproteins, and adhesin P1 genes were selected for genotyping. These SNPs were evaluated on 140 M. pneumoniae cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…Several studies have indicated that the discrimination power of four-locus MLVA is low because the unstable Mpn 1 locus is excluded (12,21,24). Therefore, to improve the discrimination power of MLVA for M. pneumoniae, a new MLVA scheme should be developed that includes additional VNTR markers such as those identified in a recent study (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that the discrimination power of four-locus MLVA is low because the unstable Mpn 1 locus is excluded (12,21,24). Therefore, to improve the discrimination power of MLVA for M. pneumoniae, a new MLVA scheme should be developed that includes additional VNTR markers such as those identified in a recent study (33).…”
Section: Discussionmentioning
confidence: 99%
“…We also reported P1 types and the prevalence of macrolide resistance-associated mutations of M. pneumoniae isolates in Yamagata, Japan between 2004 and 2013 (22). However, few reports have described the MLVA types of M. pneumoniae and examined the association between MLVA type and macrolide susceptibility in Japan (23,24). In this study, we performed MLVA typing for M. pneumoniae isolated between 2004 and 2014 in Yamagata, Japan, and evaluated the molecular epidemiological features of M. pneumoniae including P1 type and prevalence of macrolide resistance-associated mutations during an 11-year period.…”
Section: Introductionmentioning
confidence: 90%
“…To examine intrastrain copy number variation, we used archived NGS raw reads for 26 M. pneumoniae isolates, including 454 reads (average length 509 bp) for one isolate 309 reported by Kenri et al [36]; Illumina reads (251 bp each) for 15 isolates reported by Xiao et al [8]; Illumina reads (116 bp each) for two isolates reported by Li et al [37,38]; Illumina reads (95 bp each) for seven isolates reported by Lluch-Senar et al [7]; Illumina reads (36 bp each) for the strain FH reported by Touati et al [39]. We selected only seven of the 23 isolates reported by Lluch-Senar et al [7] that represented different genome size and geographic regions, instead of using all of them because their read lengths were too short (95 bp) to cover the long repeats in Mpn14-16.…”
Section: • Genome Assemblies and Ngs Data Sourcesmentioning
confidence: 99%
“…These studies expand our understanding of the VNTR variations and provide potential new MLVA schemes for M. pneumoniae geno typing. Further studies are needed of the performance of these new MLVA schemes in comparison with multilocus sequence typing [34], multiplex single nucleotide polymorphisms [39] and genome-wide single nucleotide polymorphisms and indels [7] using whole genome sequence data currently available and/or from new clinical isolates with diverse clinical and epidemiological parameters. This report presents the first successful attempt of using primarily the wealth of publicly available NGS sequences to address the fundamental questions on M. pneumoniae biology.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation